Lectures on polynomial equations: Max Noether’s Fundamental Theorem, The Jacobi Formula and Bézout’s Theorem - Płoski, Arkadiusz (Analitic and Algebraic Geometry 4, 2022)
Using some commutative algebra we prove Max Noether’s Theorem, the Jacobi Formula and B´ezout’s Theorem for systems of polynomial equations defining transversal hypersurfaces without common points at infinity.